2015
DOI: 10.1007/s13365-015-0329-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antiretroviral treatment initiation on cognition in HIV-infected individuals with advanced disease in Pune, India

Abstract: There has been a reduction in the most severe cases of HIV-associated neurocognitive disorders (HAND) with advances in antiretroviral treatment (ART). But the prevalence of milder forms of HAND still remains high. Data from systematically conducted studies on the effects of ART on cognition are scanty in India where HIV-1 clade C is prevalent. The purpose of the present study was to assess the effect of antiretroviral therapy in HIV seropositive (HIV+) individuals (n = 92) with CD4 cell counts < 200 cells/mm3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…The proportion of individuals speaking Telegu in the HIV+ group was significantly lower compared to the HIV− group, warranting cautious interpretation of the group differences in cognitive functioning. Other studies in different geographically/linguistically distinct regions of India have reported mild to moderate cognitive deficits in individuals with HIV-1 Clade C infection 11,12,24 . Our findings are consistent with prior reports of HIV-associated cognitive impairments in Clade C infected cohorts.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The proportion of individuals speaking Telegu in the HIV+ group was significantly lower compared to the HIV− group, warranting cautious interpretation of the group differences in cognitive functioning. Other studies in different geographically/linguistically distinct regions of India have reported mild to moderate cognitive deficits in individuals with HIV-1 Clade C infection 11,12,24 . Our findings are consistent with prior reports of HIV-associated cognitive impairments in Clade C infected cohorts.…”
Section: Discussionmentioning
confidence: 86%
“…Our findings are consistent with prior reports of HIV-associated cognitive impairments in Clade C infected cohorts. Of note, these studies in Karnataka 12 , Chandigarh 24 , and Pune 11 , as well as our study in Chennai, vary in their study design (e.g., presence or absence of control group), HIV disease characteristics, and assessment approach (e.g., batteries and individual tests used, language of administration). Thus, direct comparisons across studies are not possible; however, there is evidence for a general trend of HIV-associated neurocognitive disorders in diverse Indian cohorts.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These milder neurological disorders have been collectively designated HIV-associated neurocognitive disorder (HAND). Though the frequency of HAD has significantly decreased with HAART, approximately half of all HIV-infected individuals develop some form of HAND (34,55,56). One plausible explanation for HAND is decreased, but incompletely suppressed, viral replication within the central nervous system (CNS) (54,57).…”
Section: Clinical Disorders Associated With Viral Replication In Macrmentioning
confidence: 99%